Análise da pesquisa científica no setor citrícola a partir de indicadores bibliométricos - Souza, Cláudia Daniele de (Universidade Federal de São Carlos, 2013)
The citrus sector includes agriculture of citrus oranges, lemons, mandarins and their hybrids and has several extremely important economic and social in more than 100 countries in all continents around the world. While some countries have local markets for fresh fruit, as is the case in Spain, Morocco, Israel, Cuba and South Africa, others depend on processing and export as an outlet for a large part of their production, for example, Brazil, United States, China, India and Mexico. The numbers and ciphers citrus sector are expressive and reflect their relevance to the world economy, however the knowledge about the measurement of scientific and bibliometric indicators in this sector is still a gap to be filled. The objective of this dissertation is to give an overview of the scientific production related to the citrus sector between 2000 and 2010 and see what the contribution of Brazil in the same period. The methodological procedures involved some steps to a better development of research: exploratory search the international database Web of Science (WoS), with the aim to find relevant keywords, grouping of terms, preparation of the search expression, collection bibliographic records, pre-treatment of the data, with bibliometric analysis software Vantage Point and finally graphical representations with with the support of software Microsoft Office Excel, and Ucinet NetDraw. The research results were analyzed bibliometric indicators on the evolution of scientific publications, their geographic distribution in the world and Brazilian regions, mapping of institutions and actors more productive, calculation of the impact and visibility of these publications, thematic investigation of specializations and also the relationships occurring in scientific collaboration. It s concluded that research on citrus sector supports and monitors the economic competitiveness of their production regions, with the generation of highly specialized knowledge.
Keywords: Bibliometria; Produção científica; Setor citrícola; Frutas cítricas - cultivo; Indicadores bibliométricos; Citricultura; Bibliometrics; Bibliometric indicators; Scientific production; Citrus sector; Citriculture; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA